Biological Markers of Fitness Among Qualified Athletes in Greco-Roman Wrestling (Global Journal of Human-Social Science, 2021)
The article presents the dynamics of the fitness indicators among qualified athletes in Greco-Roman wrestling in the process of their pre-competition training, as a reflection of adaptive changes during performed exercises. The changing dynamics of the studied indicators and their variability during pre-competition training is a phenomenon of functional reactions of the body's internal systems. Adaptive changes in the energy systems of qualified athletes in the process of training highlight the specifics of training work in Greco-Roman wrestling. It is crucial to control these changes during a series of shock training loads of each weekly microcycle.
Keywords: greco-roman wrestling; markers; adaptation; training loads; pre-competition training